Was Piketty right? Empirics of CCC Model: Corporate Power, Consumption, Debt and Inequality - Porenta, Franci (Panoeconomicus, 2018)
This paper provides an empirical investigation into the empirics of cumulative and circular causation (CCC) model. Relying on their corporate power, corporations have stimulated the rising consumerism, which has increased both private consumption and debt. On the other hand, increasing debt has enhanced the process of rising inequality due to the lack of funding to invest in education or create savings. Rising inequality has further increased the bargaining power of capital and closed the CCC model. This paper tests the proposed theoretical model on a sample of OECD countries in the period between 1990 and 2013. We show that the growing corporate power causes increased consumption, growing household and public debt, as well as higher inequality. The paper makes several original contributions to the existing literature. First, it is the first empirical investigation of the CCC relationship. Second, it extends the knowledge about the trends of rising corporate power and consumerism at macro level. Key words: Corporate power, Consumption, Debt, Non-recursive, Cumulative circular causation, Inequality. JEL: B52, E02, P10. Da li je Piketi bio u pravu? Empirija CCC modela: korporativna moć, potrošnja, dug i nejednakost U radu je pruženo praktično ispitivanje empirije modela kumulativne i kružne uzročnosti (CCC). Oslanjajući se na svoju korporativnu moć, kompanije su podstakle rast konzumerizma, što je povećalo i privatnu potrošnju i dug. S druge strane, sve veći dug je ubrzao proces rasta nejednakosti zbog nedostatka finansijskih sredstava za ulaganje u obrazovanje ili kreiranje štednje. Rastuća nejednakost dodatno je povećala pregovaračku moć kapitala i zatvorila CCC model. U radu je testiran navedeni teorijski model na uzorku zemalja članica OECD-a u periodu između 1990. i 2013. Pokazujemo da rastuća korporativna moć uzrokuje i veću potrošnju, rast privatnog i javnog duga, kao i nejednakosti. Rad pruža nekoliko originalnih doprinosa postojećoj literaturi. Najpre, predstavlja prvo empirijsko istraživanje CCC odnosa. Zatim, proširuje znanje o trendovima rasta korporativne moći i konzumerizma na makro nivou. Ključne reči: Korporativna moć, potrošnja, dug, nerekurzivno, kumulativna kružna uzročnost, nejednakost.